PENINGKATAN HASIL BELAJAR SOAL CERITA LUAS TRAPESIUM DAN LAYANG-LAYANG DENGAN MENGGUNAKAN STRATEGI POLYA DI SEKOLAH DASAR - Hanum, Syarifah (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
The research was based on learning about the wider story trapezoid and kite using Polya strategy in class V conventional, students still had difficulty in determining the sentence about the mathematics that exist in the story. This can be overcome by Polya strategy. Subjects in this study were teachers and students of the fifth grade of primary school. The research data is in the form of the observation and documentation of the learning. The approach used in this study is a qualitative and quantitative approach, Type of Classroom Action Research. The results show that the strategy can improve learning out comes Polya story about wide trapezoid and a kite. Kata Kunci: hasil belajar; soal cerita; dan strategi polya.